Comparison of T24H-his, GST-T24H and GST-Ts8B2 recombinant antigens in western blot, ELISA and multiplex bead-based assay for diagnosis of neurocysticercosis - Ana Hernández-González (Parasites & Vectors, 2017)
Abstract Background Currently, the reference standard assay for the serodiagnosis of neurocysticercosis (NCC) is the lentil lectin-bound glycoproteins/enzyme-linked immunoelectrotransfer blot (LLGP-EITB). The main disadvantage of this technique is the complexity of obtaining and purifying the LLGP extract. This could be solved by replacement with highly specific recombinant antigens from Taenia solium. Based on previous studies, we selected and produced the recombinant Ts8B2 and T24H proteins and applied them to three diagnostic techniques: western blot (WB), enzyme-linked immunosorbent assay (ELISA) and the multiplex bead-based assay (MBA). Methods The Ts8B2 and T24H cDNA sequences were expressed in a prokaryotic system and the corresponding expression products purified; three recombinant proteins were further characterized: T24H-his, GST-T24H and GST-Ts8B2. The proteins on WB, ELISA and MBA were tested against 149 sera from patients with NCC confirmed by brain imaging, 40 sera from patients with other parasitic diseases, and 131 sera from US. individuals without evidence of neurocysticercosis (clinical/serological/brain imaging). The sensitivity and specificity of each antigen by WB were calculated by counting the number of true positive, false positive, true negative and false negative results. Using the receiver operating characteristic (ROC) curves, the cut-off values for the ELISA and MBA were established as well as the sensitivity and specificity of each assay. Results All three antigens showed a high sensitivity on WB in active NCC cases with two or more viable cysts and low sensitivity for cases with single viable cyst or calcified lesions and inactive NCC. WB showed the highest specificity and sensitivity out of the three diagnostic techniques. The recombinant T24H-his was the best diagnostic reagent in WB (100% sensitivity, 99.4% specificity), exhibiting similar results to the LLGP-EITB, against the same panel of NCC sera. The GST-T24H antigen worked better than the others in ELISA and MBA protocols (88.3 and 96.1% sensitivity, respectively and 96.5% specificity). Conclusions The sensitivity and specificity that we obtained were similar to results from a previous study using a similar recombinant antigen (rT24H), suggesting that recombinant antigens may be good alternatives to crude extracts in a variety of diagnostic techniques. Furthermore, these antigens can be applied in the development of point-of-care tests which would be useful in NCC field studies.